Nanofabrication of very-thin self-sustained reduced graphene oxide nanopores for selective protein transport - Lee, Dae Sik; Park, Seokhan; Han, Yong Duk; Lee, Jae Eun; Jeong, Hu Young; Yoon, Hyun C.; Kim, Sang Ouk; Choi, Sung Yool (22nd International Conference on Miniaturized Systems for Chemistry and Life Sciences, MicroTAS 2018, 2018)
A new self-suspending nanoporous reduced graphene membrane is designed and fabricated by employing block copolymer (BCP) lithography and dense ultrathin 15 nm-thick nanopore having area (200 micrometer x 200 micrometer) as an super-ultra-high aspect ratio of forty thousand). The preliminary nanopores concept and analysis in Adv. Mater. [1] and a fabrication process part for the device were reported at J. Biomed. Opt. [2]. Our method differs from the previous results [1-2] in the specific working method, basic material, basic design, and fabrication methods. Finally, we have confirmed that the ultrathin 15 nm-thick nanopores are strong enough to be sustain pressures until 1 atm. And they have worked well in separation of hemoglobin (Hb) from a mixed solution of two kinds of proteins, that is immunoglobulin G (IgG) and hemoglobin. They are popular proteins within human blood sample, in a very fast and alternative way. The use of free-standing reduced graphene oxide (rGO) nanosieve will give a simple but mass-producible module for the useful biomolecule isolation giving very high selective results and very fast working speed.
Keywords: Fabrication method; Fabrication process; Human blood samples; Immunoglobulin G; Mass producible; Protein transport; Reduced graphene oxides (RGO); Selective separation; Graphene oxide; Nanopores; Protein transport; Selective separation